(untitled) (Hekima Review, 2015)
The increase in demand for oil and mining products has accelerated investments in the oil and mining sectors of many African countries. However, the challenge of weak governance, weak environmental and socio-economic and political standards are more likely to make resources a curse. The discovery of more minerals in Sub-Saharan African countries is an important opportunity which needs to be well managed. Reports show that most countries in sub-Saharan Africa are rich in natural resources, yet paradoxically some of them are ranked among the poorest in the world.